2016
DOI: 10.1128/aem.00411-16
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Flavobacterium psychrophilum Isolates from Three Oncorhynchus spp. in the United States, as Revealed by Multilocus Sequence Typing

Abstract: The use of a multilocus sequence typing (MLST) technique has identified the intraspecific genetic diversity of U.S. Flavobacterium psychrophilum, an important pathogen of salmonids worldwide. Prior to this analysis, little U.S. F. psychrophilum genetic information was known; this is of importance when considering targeted control strategies, including vaccine development. Herein, MLST was used to investigate the genetic diversity of 96 F. psychrophilum isolates recovered from rainbow trout (Oncorhynchus mykiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 42 publications
5
66
0
Order By: Relevance
“…LaFrentz et al () redesigned the primers developed by Ashrafi et al () to be able to amplify the six housekeeping genes of F. columnare isolates from all four genetic groups, which will facilitate such research. Similar research has been conducted with F. psychrophilum which has increased knowledge of molecular diversity, bacterial population structure, epidemiology and host associations (Avendano‐Herrera et al, ; Knupp et al, ; Nicolas et al, ; Siekoula‐Nguedia, Blanc, Duchaud, & Calvez, ; Strepparava, Nicolas, Wahli, Segner, & Petrini, ; Van Vliet, Wiens, Loch, Nicolas, & Faisal, ).…”
Section: Discussionmentioning
confidence: 83%
“…LaFrentz et al () redesigned the primers developed by Ashrafi et al () to be able to amplify the six housekeeping genes of F. columnare isolates from all four genetic groups, which will facilitate such research. Similar research has been conducted with F. psychrophilum which has increased knowledge of molecular diversity, bacterial population structure, epidemiology and host associations (Avendano‐Herrera et al, ; Knupp et al, ; Nicolas et al, ; Siekoula‐Nguedia, Blanc, Duchaud, & Calvez, ; Strepparava, Nicolas, Wahli, Segner, & Petrini, ; Van Vliet, Wiens, Loch, Nicolas, & Faisal, ).…”
Section: Discussionmentioning
confidence: 83%
“…Nicolas et al (2008) performed a multilocus sequence analysis and showed the existence of 33 distinct sequence types, with the bacterium isolates from eels grouped in ST15. Individual sequence types within the species F. psychrophilum have been observed as both host specialists and host generalists (Avendaño-Herrera et al, 2014;Nilsen et al, 2014;Van Vliet, Wiens, Loch, Nicolas, & Faisal, 2016). According to Nicolas et al (2008), this sequence type seems to be distinct from those associated with salmonid aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…For effective development and commercialization of a vaccine to BCWD/RTFS it must be demonstrated that conferred protection is to a variety of bacterial strains. Although F. psychrophilum strain diversity continues to be characterized, it is known that at least seven F. psychrophilum serotypes exist (Dalsgaard & Madsen, ; Mata, Skarmeta, & Santos, ), and intraspecific genetic heterogeneity has been described using phage typing (Castillo, Espejo, & Middelboe, ), random amplified polymorphic DNA (RAPD) analysis (Chakroun, Grimont, Urdaci, & Bernardet, ), pulsed field gel electrophoresis (Arai, Morita, Izumi, Katagiri, & Kimura, ), restriction digestion/sequence analysis of ribosomal and housekeeping genes (Dalsgaard & Madsen, ), and MLST (Ngo et al., ; Nicolas et al., ; Van Vliet et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains used in this study included nine virulent strains of F. psychrophilum and were compared to a standard virulent strain, CSF-259-93 as a positive control (Table 1). All 10 F. psychrophilum strains were genotyped via multilocus sequence typing (MLST; Nicolas et al, 2008) in previous (Duchaud et al, 2018;Van Vliet et al, 2016) or the current/ongoing studies (Table 1) using previously described methods (Van Vliet et al, 2016) and represent seven different sequence types belonging to three clonal complexes. For virulence challenges, bacteria were cultured in tryptone yeast extract salts broth (TYES, 0.4% tryptone, 0.04% yeast extract, 0.05% calcium chloride, 0.05% magnesium sulphate, pH 7.2); following previously published protocols (LaFrentz et al, 2008;Long et al, 2013;Sudheesh & Cain, 2016).…”
Section: Bacteria and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation